Succession and the Transfer of Social Capital in Chinese Family Businesses Understanding Guanxi as a Resource - Cases, Examples and Firm Owners in Their Own Words - Ke, Xing (2018)
This is the first systematic study of the succession process of Chinese family businesses which reveals what is truly happening during the time of hand-over. In explaining the features of the Chinese way of succession, special attention is paid to the transfer of social capital and guanxi, among other cultural and socioeconomic contexts, which could impact the behaviours and decisions of the family business stakeholders. Carefully selected 63 cases of family firms and the authentic words and experiences of the founders and their second generation are of high relevance in helping the readers to understand Chinese family businesses and their successions as well as to learn from their successes or failures.